DAUGHTERS OF THE SUN : EMPRESSESS, QUEENS, AND BEGAMS OF THE MUGAL EMPIRE - IRA MUKHOTY (NEW DELHI ALEPH, 2018)
The very first attempt to chronicle the women who played a vital role in building the Mughal empire, daughters of the sun is an illuminating and gripping history of a little known aspect of the most magnificent dynasty the world has ever known.
Keywords: ROYAL WOMEN-MUGHAL EMPIRE; MEDIEVAL INDIA